Immunogenicity and safety of a novel seasonal influenza preservative-free vaccine manufactured in Kazakhstan: Results of a randomized, comparative, phase II clinical trial in adults. Issue 3 (4th March 2018) - Sarsenbayeva, Gulbanu; Volgin, Yevgeniy; Kassenov, Markhabat; Issagulov, Timur; Bogdanov, Nikolay; Sansyzbay, Abylay; Stukova, Marina; Buzitskaya, Zhanna; Кulmagambetov, Ilyas; Davlyatshin, Timur; Khairullin, Berik
ABSTRACT: Background: The study was aimed at comparative evaluation of seasonal influenza vaccine RIBSP versus commercial vaccine VAXIGRIP® for immunogenicity and safety in the course of clinical trial phase II on healthy volunteers aged 18–60 years.Methods: The trial involved 150 subjects in randomized 2:1 groups that received either RIBSP vaccine or comparator vaccine VAXIGRIP®. One dose (0.5 ml) of either vaccine contained 15 μg of hemagglutinin of each influenza virus strain recommended by WHO for the Northern hemisphere in 2016–2017 flu season. The observation period lasted 21 day. The trial was registered at ClinicalTrials.gov identifier NCT 03016143.Results: Assessment of immunogenic activity of the vaccine under study showed that in 21 day the portion of participants with 4-fold seroconversions was 87.0% to A/H1N1; 63.0% to A/H3N2 and 59.0% to B virus. Antibody titer increase factor in the group of subjects that received RIBSP vaccine was 23.3 for A/H1N1; 4.4 for A/H3N2 and 4.5 for B virus. The volunteers that received RIBSP vaccine demonstrated 95% seroprotection level against A/H1N1; 84% against A/H3N2 and 80% against B virus. RIBSP vaccine met the CHMP criteria of the Committee for Medicinal Products for Human Use (CPMP/BWP/214/96). In the course of evaluating the vaccine safety no serious undesirable effects were recorded. All changes of laboratory data were slight and single in most cases. All recorded local reactions have been light in character and these have been predicted reactions observed at vaccination against influenza.Conclusion: Comparison of the allantoic inactivated split vaccine obtained in vaccines RIBSP and VAXIGRIP®, showed similar immunogenic activity. Both vaccines were safe for the study participants.